Research-Community Partnerships to Support Teacher Professional Learning - Wade-Jaimes, Katherine; Askew, Rachel; Johnson, Cullen; Butler, Chuck (Innovations in Science Teacher Education, 2023)
Providing ongoing support for inservice teachers is a challenge faced by school districts, educational organizations, and colleges of education everywhere. In this article, we describe a partnership between a community-based educational organization and educational researchers designed to provide professional development and support for science and math teachers while also supporting youth participating in a summer STEM program. Originating from an identified need of the community organization to better support youth STEM identity in their programming and rooted in a framework of STEM identity and equity in STEM, this partnership leveraged resources from different groups and was shown to be beneficial to the community organization, educational researchers, teachers, and youth. It this article, we discuss the logistics of this partnership and how it was implemented during a summer program, provide outcomes from youth and teachers, and include suggestions for the development of similar partnerships.